The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pssc.201084136
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo‐self‐organized topological phases in glassy selenides for IR photonics

Abstract: Network‐forming cluster approach is applied to As‐Se and Ge‐Se glasses to justify their tendency to self‐organization. It is shown that reversibility windows determined by temperature‐modulated differential scanning calorimetry using short‐term aged or as‐prepared samples do not necessary coincide with self‐organized phase in these materials. The obtained results testify also pseudo‐self‐organization phenomenon in Ge‐Se glasses: over‐constrained outrigger raft structural units built of two edge‐ and four corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…3, the scan rate was 5 • C/min which is quite close to 3 • C/min used as a typical MDSC scan rate by Dash et al 2 At such low scan rates (2-5 • C/min), the conclusions drawn from MDSC and conventional DSC would be quite similar, which has been convincingly proved at the example of As/Ge-Se glasses. 3,5,6 The narrowing of glass transition range W as a result of physical aging or annealing was also observed previously in pure Se, 7 a number of Se-based glasses, 8,9 and even organic polymers. 10 Moreover, in As-Se glasses, this narrowing was accompanied by changes in the asymmetry of non-reversing heat flow (∆H nr ) measured at 2 • C/min scan rate after ∼20 years of dark storage at room temperature.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…3, the scan rate was 5 • C/min which is quite close to 3 • C/min used as a typical MDSC scan rate by Dash et al 2 At such low scan rates (2-5 • C/min), the conclusions drawn from MDSC and conventional DSC would be quite similar, which has been convincingly proved at the example of As/Ge-Se glasses. 3,5,6 The narrowing of glass transition range W as a result of physical aging or annealing was also observed previously in pure Se, 7 a number of Se-based glasses, 8,9 and even organic polymers. 10 Moreover, in As-Se glasses, this narrowing was accompanied by changes in the asymmetry of non-reversing heat flow (∆H nr ) measured at 2 • C/min scan rate after ∼20 years of dark storage at room temperature.…”
supporting
confidence: 75%
“…15 The threshold time depends essentially on T a , decreasing when T a approaches T g ; i.e., t th is different for the glasses with different T g aged at the same temperature. As a result, the isochronal aging-induced changes in T g (especially as small as 2-4 • C) 2 T g , which varies from ∼40 • C for pure Se to about ∼70 • C for Ge 6 Se 94 glasses (see Fig. 4 in Ref.…”
mentioning
confidence: 99%
“…Although some other models [335,371] with a weaker theoretical basis have argued that the existence of the IP remains elusive, albeit contradicted by the variety of experimental signatures, there is a strong theoretical and numerical indication that RW or IP glasses display a particular relaxation kinetics manifesting in ∆H nr that leads to anomalous properties in different physical properties (Fig. 40).…”
Section: Alternative Signatures Of Rwsmentioning
confidence: 99%
“…107 The observation of these spectacular changes occurring within the x c1 < x < x c2 range requires special care in sample preparation because it has been shown that measurements are highly sensitive to dryness or homogeneity. 107,109,110 As an unfortunate consequence, there have been reported statements challenging 82,111,112 the existence of the intermediate phase.…”
Section: Introductionmentioning
confidence: 99%